2019
DOI: 10.1371/journal.pone.0224803
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two thermophilic cellulases from Talaromyces leycettanus JCM12802 and their synergistic action on cellulose hydrolysis

Abstract: Talaromyces leycettanus JCM12802 is a great producer of thermophilic glycoside hydrolases (GHs). In this study, two cellulases (TlCel5A and TlCel6A) belonging to GH5 and GH6 respectively were expressed in Pichia pastoris and functionally characterized. The enzymes had acidic and thermophilic properties, showing optimal activities at pH 3.5–4.5 and 75–80°C, and retained stable at temperatures up to 60°C and over a broad pH range of 2.0−8.0. TlCel5A and TlCel6A acted against several cellulose substrates with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…The GH16 elongating β-transglycosylase from Paecilomyces thermophila (PtBgt16A), which also performed hydrolysis of mixed linkages, showed a pH optimum of 5.5 and a temperature optimum of 60 • C [18]. Additionally, a recent study showed the GH5A enzyme from Talaromyces leycettanus JCM12802 to have a high specific activity on a mixed-linkage substrate [19]. The enzyme showed a pH optimum of 3 and a temperature optimum of 75 • C. In contrast, Exg-D showed a broad pH optimum from 5.5 to 7 and a temperature optimum from 40 to 60 • C. The broad pH and temperature optima of Exg-D enzyme make it a potential candidate for the hydrolysis of licheninor β-glucan-containing biomass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GH16 elongating β-transglycosylase from Paecilomyces thermophila (PtBgt16A), which also performed hydrolysis of mixed linkages, showed a pH optimum of 5.5 and a temperature optimum of 60 • C [18]. Additionally, a recent study showed the GH5A enzyme from Talaromyces leycettanus JCM12802 to have a high specific activity on a mixed-linkage substrate [19]. The enzyme showed a pH optimum of 3 and a temperature optimum of 75 • C. In contrast, Exg-D showed a broad pH optimum from 5.5 to 7 and a temperature optimum from 40 to 60 • C. The broad pH and temperature optima of Exg-D enzyme make it a potential candidate for the hydrolysis of licheninor β-glucan-containing biomass.…”
Section: Discussionmentioning
confidence: 99%
“…This distinction between GH16 enzymes and Exg-D emphasised the novelty of the mechanism employed by Exg-D during the hydrolysis of mixed-linkage oligosaccharides/substrates. In addition, Exg-D was also highly active on cello-oligosaccharides, and it employed the well-studied processive mechanism of exoglucanases [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant enzyme was successfully expressed by P. pastoris, with a main product that shows a molecular size of about 50 kDa. The recombinant Plasmid Cel6A selected was linearized with the enzyme BamHIO recombinant plasmid, pLIPI-TrCel6A, carrier of the T. r e e s e i Cel6A gene (TrCel6A) integrated into the genome of P. pastoris SMD1168H [50].…”
Section: Recombinant Fungal Cellulases Produced By Different Expression Systemsmentioning
confidence: 99%
“…Talaromyces leycettanus JCM12802 is a typical thermophilic fungus with an optimum temperature for growth at 40 ℃, producing a wide range of thermostable glycoside hydrolases, such as cellulase, β-glucosidase, and mannanase [ 23 25 ]. In this study, a novel thermostable glucoamylase Tl Ga15B from T. leycettanus JCM12802 was expressed and characterized.…”
Section: Introductionmentioning
confidence: 99%